2023
DOI: 10.1049/ipr2.12780
|View full text |Cite
|
Sign up to set email alerts
|

A graph‐based edge attention gate medical image segmentation method

Abstract: For the purpose of solving the problems of missing edges and low segmentation accuracy in medical image segmentation, a medical image segmentation network (EAGC_UNet++) based on residual graph convolution UNet++ with edge attention gate (EAG) is proposed in the study. With UNet++ as the backbone network, the idea of graph theory is introduced into the model. First, the dropout residual graph convolution block (DropRes_GCN Block) and the traditional convolution structure in UNet++ are used as encoders. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In such scenarios, parameter tuning is of utmost importance, as emphasized by Yu et al (2023). To overcome these challenges, optimizations such as integrating edge features as suggested by Hao and Li (2023) or utilizing neural networks as implemented by Meng et al (2021) could prove to be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In such scenarios, parameter tuning is of utmost importance, as emphasized by Yu et al (2023). To overcome these challenges, optimizations such as integrating edge features as suggested by Hao and Li (2023) or utilizing neural networks as implemented by Meng et al (2021) could prove to be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…We introduce an improved edge feature attention mechanism for retinal images to enhance edge information and address these gaps. Inspired by the approach in [ 35 ] and designed for 2D images, our edge attention (EA) block combines the structure with the Canny operator to boost edge features. In Figure 4 , represents the feature mapping output at the i th layer, characterised by feature maps with dimensions , where, is the number of channels and denotes the size of each feature map.…”
Section: Methodsmentioning
confidence: 99%
“…Attention mechanisms empower models to selectively focus on crucial features or regions, enhancing performance in tasks like image segmentation. Various studies have suggested incorporating attention blocks or modules into the U-Net’s encoder or decoder [ 35 , 36 , 37 , 38 ]. These attention mechanisms may utilise techniques such as channel attention, spatial attention, or self-attention.…”
Section: Related Workmentioning
confidence: 99%
“…Yu et al [44] maintained the topology of vessels by creating edges and predicting links between various nodes, which were generated from semantic information extracted using U-Net. Hao et al [45] presented a new framework called EAGC_UNet++, a graph-based edge attention gate, for medical image segmentation. By leveraging a combination of a residual graph convolution network, UNet++ and edge attention gates (EAG), the proposed model has demonstrated significant improvements in the accuracy of medical image segmentation and tackled the problem of missing edges.…”
Section: Gcn-based Methodsmentioning
confidence: 99%